2013
DOI: 10.1097/brs.0b013e318261ea6f
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Profile of NF-κB/p50, NF-κB/p65, MMP-9, MMP-2, and u-PA in Experimental Cervical Spondylotic Myelopathy

Abstract: There is a strong correlation between the immunoexpression of NF-κB/p50, NF-κB/p65, MMP-2, MMP-9, u-PA, and CSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Moreover, MMP-9 has been implicated in promoting blood-brain barrier disruption and subsequent exaggeration of the inflammatory process in different CNS diseases. Interestingly, a recent study on a new rabbit model of CSM (Klironomos and others 2011) revealed that the MMP-9 immunoreactivity was significantly higher in spinal cord tissue from rabbits that underwent chronic compression of the cervical spinal cord for 20 weeks (Karadimas and others 2012a). Unfortunately, these authors did not evaluate the role of MMP-9 under the chronic progressive compression of the cervical spinal cord by blocking or deleting MMP-9.…”
Section: Current Knowledge In Cervical Spondylotic Myelopathy Pathobimentioning
confidence: 99%
“…Moreover, MMP-9 has been implicated in promoting blood-brain barrier disruption and subsequent exaggeration of the inflammatory process in different CNS diseases. Interestingly, a recent study on a new rabbit model of CSM (Klironomos and others 2011) revealed that the MMP-9 immunoreactivity was significantly higher in spinal cord tissue from rabbits that underwent chronic compression of the cervical spinal cord for 20 weeks (Karadimas and others 2012a). Unfortunately, these authors did not evaluate the role of MMP-9 under the chronic progressive compression of the cervical spinal cord by blocking or deleting MMP-9.…”
Section: Current Knowledge In Cervical Spondylotic Myelopathy Pathobimentioning
confidence: 99%
“…Cervical radicular pain is pain perceived in the upper extremity, shooting or electric in quality, caused by irritation and/or injury of cervical spinal nerves (19,20). Cervical radicular pain may be caused either by disc herniation or compression due to other ailments in the cervical spine, or chemical irritation (18)(19)(20)(21)(22)(23)(24).…”
Section: Participantsmentioning
confidence: 99%
“…Although the tumor necrosis factor-a, the mitogenactivated protein kinase pathways and the nuclear factor-j B [45] have been identified as potential apoptotic signaling pathways in CSM, there is also evidence that blocking the FasL signaling pathway results in decreased levels of cellular apoptosis and improved functional outcomes in CSM. It is obvious that only when identification of the extra and intracellular apoptotic pathways implicated in CSM is complete, we will be able to develop novel neuroprotective treatments for this disease.…”
Section: Apoptotic Cell Deathmentioning
confidence: 99%